Dependence of the number and frequency of spikes in the "explosions" " of the RC-parameter analog integrator - Medetov, B.ZH.; Albanbay, N.; Nalibayev, Y.D.; Asanov, G.S. (Recent Contributions to Physics, 2014)
This paper studies the experimental aspects influencing the formation of a cluster of signals consisting of two linearly negatively associated neurons. The paper shows that the frequency of "explosions", "spikes", as well as the number of "spikes" in the "explosions" depend on the RC - parameter analog integrator used in the experiment. The results of processing the experimental data, the frequency of "explosions" and "spikes" depend on RC - parameter power law. Results obtained in the experiment, the frequency of formation of "explosions" and the frequency of spikes is quite dependent on the RC - parameter, in particular from the resistor used in the analog integrator. And also conducted approximation show that the data depending analytically very well described by the function